2022
DOI: 10.3390/su14116453
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Recovery from Traffic Restriction Policies during the COVID-19 through the Perspective of Regional Differences and Sustainable Development: Based on Human Mobility Data in China

Abstract: In the post-epidemic era, balancing epidemic prevention and control with sustainable economic development has become a serious challenge for all countries around the world. In China, a range of interventions include detection policies, clinical treatment policies, and most notably, traffic policies have been carried out for epidemic prevention and control. It has been widely confirmed that massive traffic restriction policies effectively brought the spread of the pandemic under control. However, restrictions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Many studies point to the lockdown measures [11] and changes in tourist psychology [38] as the main reasons for the negative impact of the pandemic on traffic volume. Specifically, due to the concern of potential travelers about the infection, road traffic volume tended to decrease with the increase of confirmed COVID-19 cases [19]. Several studies have confirmed the existence of this adverse effect in regions such as China [8], the United States [39], and Korea [40].…”
Section: Covid-19 and Climate Suitabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies point to the lockdown measures [11] and changes in tourist psychology [38] as the main reasons for the negative impact of the pandemic on traffic volume. Specifically, due to the concern of potential travelers about the infection, road traffic volume tended to decrease with the increase of confirmed COVID-19 cases [19]. Several studies have confirmed the existence of this adverse effect in regions such as China [8], the United States [39], and Korea [40].…”
Section: Covid-19 and Climate Suitabilitymentioning
confidence: 99%
“…Because of the strong relationship between traffic volume and economic development [18], the recovery of traffic volume from the impact of COVID-19 has an essential role in promoting economic recovery [19]. Therefore, a feasible way to recover traffic volume has been the focus of recent academic discussions.…”
Section: Introductionmentioning
confidence: 99%
“…The Gross Domestic Product (GDP) [8] is the market value of the production results of all economic activities in a region over a certain period of time. The GDP is an important indicator to measure urban development, and its development can reflect the effectiveness of the implementation of urban economic policies in improving urban economic development [9] . Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Li 22 concludes that the Chinese government successfully assessed public risk and launched a clear and timely vaccination policy. Yawen 23 explores how to strike a balance between epidemic prevention and control and sustainable economic development, and proposes that China dynamically adjusts the intensity of transportation restrictions and economic stimulus policies according to regional differences.…”
Section: Introductionmentioning
confidence: 99%